Penerapan SCADA dan IoT Menggunakan PLC Sebagai Kontrol Motor AC untuk Pembelajaran Praktikum SMK - Dadan Nurdin Bagenda; Noor Cholis Basjaruddin (Gema Teknologi, 2022)
The problem at the current Vocational High School that often arises is the unavailability of the Supervisory Control And Data Acquisition (SCADA) practicum module, to control AC Motor which can also be monitored online (IoT support) to support industry 4.0. The following solutions: (1). The developed module must be remotely controlled with industry standards; (2). The method used during the practicum is the problem-based-learning (PBL) method. To implement the above problem, a PLC that support SCADA and IoT (MQTT) was chosen. To introduce SCADA and IoT to students, we learned how to operating a simple industry-standard SCADA software and IoT (Ubidots). Post-training from the results of the questionnaire for vocational students, it was seen an average increase in knowledge of 56% compared to before training, a min 42% increase in PBL understanding, and a max 64% increase in knowledge of "Wonderware Intouch" as one of the Industry Standard SCADA